Penetapan Harga Pokok Produksi dengan Metode Full Costing sebagai Dasar Penetapan Harga Jual pada Pabrik Tempe Barokah Di Desa Bukkolan Kabupaten Situbondo - Agustin, Dwi Putri; Ade Irma Suryani Lating (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Barokah Tempe Factory is the only tempeh business in Bukkolan Village, Situbondo Regency, with a fairly consistent production scale. However, in calculating the cost of production and setting the selling price, it is still based on estimates and follows market prices, which has the potential to cause losses. This research aims to calculate the cost of production using the Full Costing method and set the selling price using the Cost Plus Pricing method at the Barokah Tempe Factory. This research uses a qualitative method with a case study approach. The data used includes primary data from interviews with the factory owner and secondary data obtained from previous research.The results of the research on the calculation of the cost of production show a difference between the calculation according to the company and the full costing method, where the calculation according to the company yielded a smaller result compared to the full costing method. The results also show that the selling price set by the company is cheaper than the one using the Cost Plus Pricing method. Therefore, it is recommended that the Barokah Tempe Factory implement systematic cost recording and calculation using the Full Costing and Cost Plus Pricing methods to obtain an accurate cost of production calculation and an accurate selling price, thereby enabling optimal profit generation.